Putting teacher evaluation systems on the map: An overview of states’ teacher evaluation systems post–Every Student Succeeds Act - Close, Kevin; Amrein-Beardsley, Audrey; Collins, Clarin (Education Policy Analysis Archives, 2020)
The Every Students Succeeds Act (ESSA) loosened the federal policy grip over states’ teacher accountability systems. We present information, collected via surveys sent to state department of education personnel, about all states’ teacher evaluation systems post–ESSA, while also highlighting differences before and after ESSA. We found that states have decreased their use of growth or value-added models (VAMs) within their teacher evaluation systems. In addition, many states are offering more alternatives for measuring the relationships between student achievement and teacher effectiveness besides using test score growth. State teacher evaluation plans also contain more language supporting formative teacher feedback. States are also allowing districts to develop and implement more unique teacher evaluation systems, while acknowledging challenges with states’ being able to support varied systems, as well as incomparable data across schools and districts in effect.